Infantile hypertrophic pyloric stenosis in patients with esophageal atresia. Issue 9 (16th April 2020) - ten Kate, Chantal A.; Brouwer, Rutger W. W.; van Bever, Yolande; Martens, Vera K.; Brands, Tom; van Beelen, Nicole W. G.; Brooks, Alice S.; Huigh, Daphne; van der Helm, Robert M.; Eussen, Bert H. F. M. M.; van IJcken, Wilfred F. J.; IJsselstijn, Hanneke; et al.
Abstract: Background: Patients born with esophageal atresia (EA) have a higher incidence of infantile hypertrophic pyloric stenosis (IHPS), suggestive of a relationship. A shared etiology makes sense from a developmental perspective as both affected structures are foregut derived. A genetic component has been described for both conditions as single entities and EA and IHPS are variable components in several monogenetic syndromes. We hypothesized that defects disturbing foregut morphogenesis are responsible for this combination of malformations. Methods: We investigated the genetic variation of 15 patients with both EA and IHPS with unaffected parents using exome sequencing and SNP array‐based genotyping, and compared the results to mouse transcriptome data of the developing foregut. Results: We did not identify putatively deleterious de novo mutations or recessive variants. However, we detected rare inherited variants in EA or IHPS disease genes or in genes important in foregut morphogenesis, expressed at the proper developmental time‐points. Two pathways were significantly enriched ( p < 1 × 10 −5 ): proliferation and differentiation of smooth muscle cells and self‐renewal of satellite cells. Conclusions: None of our findings could fully explain the combination of abnormalities on its own, which makes complex inheritance the most plausible genetic explanation, most likely in combination with mechanical and/or environmental factors. As we did not find one defining monogenetic cause for the EA/IHPS phenotype, the impact of the corrective surgery could should be further investigated.